La ranita verde - Camacho Euribe De Lázaro, Yanina Del Rosario (2019)
In order to draw up and write text we have to consider the difficulty a descriptive text has which is subordinated to another text typology that is the narration, in that we have to identify the main part of the message to infer or to express in the context of a description._x000D_ For a description it is necessary to consider the three main points, such as the hierarchy in the organization, the progression through the word’s selection of the olifferent contexts from which a description corresponds, for Shekel (1972),_x000D_ The descriptive process consists of three parts: the observation, relation among the elements, selection of data. In a description we also have to consider the locations where the characters are, the place where they are._x000D_ In every text we have to consider the whole characters that participate, conducting the learner to a better comprehension since the learning – teaching process with questions and answers, always valuing the effort he/her description, using the language properly. The learning – teaching process is har, accurate and brief, considering the most favorable strategies, methods and techniques.